Evaluation of aerosol transmission risk during home quarantine under different operating scenarios: A pilot study. (November 2022) - Cheung, Toby; Li, Jiayu; Goh, Jiamin; Sekhar, Chandra; Cheong, David; Tham, Kwok Wai
Abstract: SARS-CoV-2 has been recognized to be airborne transmissible. With the large number of reported positive cases in the community, home quarantine is recommended for the infectors who are not severely ill. However, the risks of household aerosol transmission associated with the quarantine room operating methods are under-explored. We used tracer gas technique to simulate the exhaled virus laden aerosols from a patient under home quarantine situation inside a residential testbed. The Sulphur hexafluoride (SF6 ) concentration was measured both inside and outside the quarantine room under different operating settings including, air-conditioning and natural ventilation, presence of an exhaust fan, and the air movement generated by ceiling or pedestal fan. We calculated the outside-to-inside SF6 concentration to indicate potential exposure of occupants in the same household. In-room concentration with air-conditioning was 4 times higher than in natural ventilation settings. Exhaust fan operation substantially reduced in-room SF6 concentration and leakage rate in most of the ventilation scenarios, except for natural ventilation setting with ceiling fan. The exception is attributable to the different airflow patterns between ceiling fan (recirculates air vertically) and pedestal fan (moves air horizontally). These airflow variations also led to differences in SF6 concentration at two sampling heights (0.1 m and 1.7 m) and SF6 leakage rates when the quarantine room door was opened momentarily. Use of natural ventilation rather than air-conditioning, and operating exhaust fan when using air-conditioning are recommended to lower exposure risk for home quarantine. A more holistic experiment will be conducted to address the limitations reflected in this study. Highlights: Aerosol transmission risk for different home quarantine operating scenarios. Test conditions: AC vs NV, presence of exhaust fan, and ceiling fan vs pedestal fan. Tracer gas concentration in AC settings was 4 times higher than in NV settings. Operation of exhaust fan reduced in-room SF6 concentration and transmission risk. Airflow variation from ceiling and pedestal fans led to different risk potentials.